Corrosion Behavior of Pure Cr, Ni, and Fe Exposed to Molten Salts at High Temperature - O. Sotelo-Mazón; C. Cuevas-Arteaga; J. Porcayo-Calderón; V.M. Salinas Bravo; G. Izquierdo-Montalvo (Advances in Materials Science and Engineering)
Corrosion resistance of pure Fe, Cr, and Ni materials exposed in NaVO3 molten salt at 700°C was evaluated in static air during 100 hours. The corrosion resistance was determined using potentiodynamic polarization, open circuit potential, and lineal polarization resistance. The conventional weight loss method (WLM) was also used during 100 hours. The electrochemical results showed that Fe and Cr have a poor corrosion resistance, whereas pure Ni showed the best corrosion performance, which was supported by the passive layer of NiO formed on the metallic surface and the formation of Ni3V2O8 during the corrosion processes, which is a refractory compound with a higher melting point than that of NaVO3, which reduces the corrosivity of the molten salt. Also, the behavior of these materials was associated with the way in which their corresponding oxides were dissolved together with their type of corrosion attack. Through this study, it was confirmed that when materials suffer corrosion by a localized processes such as pitting, the WLM is not reliable, since a certain amount of corrosion products can be kept inside the pits. The corroded samples were analyzed through scanning electron microscopy.